Taḥlīlu Uslūbi li Tarjamati Fatḥi al Mu’īn li Tarqiyyati Fahmi al Ṭhullābi fī Ma’hadi al Bāqiyāti al Ṣāliḥāti Kuwālā Tungkāl Jāmbi - Nadyatunnisa, Nadyatunnisa; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to discuss the translation style in the Islamic Boarding School Al-Baqiyatushhalihat Kuala Tungkal-Jambi. Specifically the objectives of this researcher are: 1) to find out the style translation (uslub) used in the Al-Baqiyatushhalihat Islamic Boarding School 2) to find out the advantages and disadvantages of the methods used in the Al Baqiyatushhalihat Islamic boarding school 3) What are the efforts of the teachers (asatidz) to increase understanding of the book. This research is a type of field research field research, namely research where data collection is carried out in the field, such as in community environment, institutions and social organizations and government agencies. This research is a qualitative research that is a research that aims to explain social phenomena or a event. This is in accordance with the definition of qualitative research, namely a research that produces descriptive data in the form of written or spoken words from people and from observable behavior. The research pattern that the researcher uses is a qualitative pattern, namely observing people (subjects) in their environment, interacting with them, trying to understand their language and their interpretation of the world around them. While the type of research used is descriptive research. Descriptive research is a type of research that provides an overview or description of a situation as clearly as possible without any treatment of the object researched. The results of the study explain that 1) Style (Uslub) used in the Al-Baqiyatushhalihat Islamic boarding school is a literal translation method 2) The advantage of translation is knowing grammar rules such as nahwu sharf and the drawback is that it is still difficult to find the essence of the discussion 3) The efforts of the ustadz increases the understanding of the book by scientific discussion (bahsul masail).The conclusion that the translation used is the translation of harfian and bahsul masail is an attempt by ustadz to increase understanding of the book